COVID-19 aus Sicht der Praxen und Notaufnahmen - Herold, Tobias; Wörnle, Markus; Schelling, Jörg (DMW - Deutsche Medizinische Wochenschrift, 2020)
COVID-19 challenges GP practice and emergency rooms across Germany. In addition to hygiene, the correct assignment of patients to outpatient, inpatient or intensive care management is difficult. This article provides an overview of aspects of initial care, management and risk assessment in COVID-19 patients. The care of corona infected patients can be improved at the interface between outpatient and inpatient care. There can be no “business as usual” after the crisis! Age, male sex and overweight are among the most important risk factors for serious corona disease. Poor oxygen saturation (< 88 %) and increased signs of inflammation (CRP > 97 mg/l and/or IL-6 > 80 pg/ml) indicate a critical course and should be determined in symptomatic patients. Only through regular dialogue between hospital and practice can meaningful decisions be made to slowly move from individual cases to a basic care structure.
Keywords: COVID-19; Notaufnahme; Hausarztpraxis; Primärversorgung